Comparative Civil Service Systems in the 21st Century
X, 373 p.
Keywords: This revised and expanded edition of a benchmark collection compares how civil services around the world have adapted to cope with managing public services in the 21st century. The volume provides insights into multi-level governance, juridification and issues of efficiency and responsiveness as well as exploring the impact of fiscal austerity.